Sex differences in psychiatric disorders: what we can learn from sex chromosome aneuploidies. (January 2019) - Green, Tamar; Flash, Shira; Reiss, Allan
Abstract The study of sexual dimorphism in psychiatric and neurodevelopmental disorders is challenging due to the complex interplay of diverse biological, psychological, and social factors. Males are more susceptible to neurodevelopmental disorders including intellectual disability, autism spectrum disorder, and attention-deficit activity disorder. Conversely, after puberty, females are more prone to major depressive disorder and anxiety disorders compared to males. One major biological factor contributing to sex differences is the sex chromosomes. First, the X and Y chromosomes have unique and specific genetic effects as well as downstream gonadal effects. Second, males have one X chromosome and one Y chromosome, while females have two X chromosomes. Thus, sex chromosome constitution also differs between the sexes. Due to this complexity, determining genetic and downstream biological influences on sexual dimorphism in humans is challenging. Sex chromosome aneuploidies, such as Turner syndrome (X0) and Klinefelter syndrome (XXY), are common genetic conditions in humans. The study of individuals with sex chromosome aneuploidies provides a promising framework for studying sexual dimorphism in neurodevelopmental and psychiatric disorders. Here we will review and contrast four syndromes caused by variation in the number of sex chromosomes: Turner syndrome, Klinefelter syndrome, XYY syndrome, and XXX syndrome. Overall we describe an increased rate of attention-deficit hyperactivity disorder and autism spectrum disorder, along with the increased rates of major depressive disorder and anxiety disorders in one or more of these conditions. In addition to contributing unique insights about sexual dimorphism in neuropsychiatric disorders, awareness of the increased risk of neurodevelopmental and psychiatric disorders in sex chromosome aneuploidies can inform appropriate management of these common genetic disorders.